Evidence for a variable Ultrafast Outflow in the newly discovered Ultraluminous Pulsar NGC 300 ULX-1. Issue 3 (20th June 2018) - Kosec, P; Pinto, C; Walton, D J; Fabian, A C; Bachetti, M; Brightman, M; Fürst, F; Grefenstette, B W
ABSTRACT: Ultraluminous pulsars are a definite proof that persistent super-Eddington accretion occurs in nature. They support the scenario according to which most Ultraluminous X-ray Sources (ULXs) are super-Eddington accretors of stellar mass rather than sub-Eddington intermediate mass black holes. An important prediction of theories of supercritical accretion is the existence of powerful outflows of moderately ionized gas at mildly relativistic speeds. In practice, the spectral resolution of X-ray gratings such as RGS onboard XMM–Newton is required to resolve their observational signatures in ULXs. Using RGS, outflows have been discovered in the spectra of three ULXs (none of which are currently known to be pulsars). Most recently, the fourth ultraluminous pulsar was discovered in NGC 300. Here we report detection of an ultrafast outflow (UFO) in the X-ray spectrum of the object, with a significance of more than 3σ, during one of the two simultaneous observations of the source by XMM–Newton and NuSTAR in December 2016. The outflow has a projected velocity of 65 000 km s −1 (0.22c) and a high ionization factor with a log value of 3.9. This is the first direct evidence for a UFO in a neutron star ULX and also the first time that this evidence in a ULX spectrum is seen in both soft and hard X-ray data simultaneously. We find no evidence of the UFO during the other observation of the object, which could be explained by either clumpy nature of the absorber or a slight change in our viewing angle of the accretion flow.